Thermodynamics : an engineering approach. - Çengel, Yunus A.; Boles, Michael A.; Kanoğlu, Mehmet (McGraw Hill, 2024)
'Thermodynamics: An Engineering Approach,' covers the basic principles of thermodynamics while presenting a wealth of real-world engineering examples, so students get a feel for how thermodynamics is applied in engineering practice. This text helps students develop an intuitive understanding by emphasizing the physics and physical arguments. This title explores the various facets of thermodynamics through careful explanations of concepts and use of numerous practical examples and figures, having students develop necessary skills to bridge the gap between knowledge, and the confidence to properly apply their knowledge.